Corporate Financialization and Stock Price Crash Risk: Evidence From China’s Listed Companies - Liu, Tingge (2022)
Based on the financial data of Chinese A-share listed firms for the period from 2008 to 2020, this paper explores the relationship between corporate financialization and stock price crash risk. Using the fixed effect model, this paper empirically tests the impact of the financialization of listed companies on the risk of stock price crashes. The regression results show that the increase in the level of corporate financialization increases the risk of stock price crashes. In the baseline results, the stock price crash risk will increase by about 9.76%-11.46% standard deviation for every increase of one standard deviation in corporate financial investment. In addition, the results of robustness checks of adding more control variables and using an instrumental approach are consistent with the baseline results.